The Mediating Effect of Ethical Perception on the Relationship between Tax Service and Tax Compliance Behavior Using Baron and Kenny and Bootstrapping Method (Journal of Business Management and Accounting, 2019)
The main purpose of this study is to examine themediating and indirect effects of ethical perception in tax service on tax compliance behaviour. The study used cross-sectional survey design to collect primary data from individual taxpayers in the southern region of Peninsular Malaysia. Data was analysed with Statistical Package for the Social Science (SPSS). Results indicate that partial mediation was supported by adopting Baron and Kenny method. However, there is almost no mediation by using bootstrapping method. It showed that ethical perception of individual taxpayers differ across individuals and these differences matter in significant ways particularly in their tax compliance decisions. Therefore, IRB should provide better tax service to individual taxpayers in order to enhance their tax ethics and compliance. This may increase tax revenue and reduce the budget deficit without raising tax rates. This research results provide valuable information for the IRB and it is useful for tax policy development.